MODEL OF CIVIL SERVANT LECTURER PENSION FUND CALCULATION USING THE ENTRY AGE NORMAL METHOD IN A PUBLIC UNIVERSITY - Rahmienda Maha, Annisa
The pension fund program is a type of long-term planning that aims to provide living expenses for civil servants after retirement. In Indonesia, pension funds are calculated based on the last civil servant salary. As a result, there is an imbalance between the accumulated contributions collected during service and the pension benefits paid for life. This resulted in an increase in the burden on the government budget to meet the adequacy of pension funds. In this research, a model is used to determine civil servant pension funds based on the average salary of the last 14 years using the Entry Age Normal method. The EAN method is a funding method, and calculations are based on the age of participants starting employment up to regular retirement age. The EAN approach is more profitable since the normal cost made by each pension fund participant are more constant because the benefit cost is first determined and then split by the remaining service years in an annuity method. The first step in this research is to build a model to predict the final rank of employees which is generally quite diverse. Then calculate the retirement benefits based on the average of the last salary and the last salary. After that calculate the normal costs using the EAN method. The final step is to predict the amount of pension funds that the government must provide to public universities over the next 20 years, which takes into account the prediction of the last rank of civil servants, the percentage of salary increases, and the candidates for new civil servants. The new employee of civil senvants data set was created using the Poisson Distribution, where the parameter values were obtained by analyzing sample data of PNS for the last 30 years. In this study, the calculation of pension benefits based on the final average salary for the last 14 years produces a relatively smaller value than the calculation of benefits based on the last salary and for normal contributions shows that each participant has a different normal contribution amount, depending on the benefit costs and retirement age, the closer to retirement age, the greater the nominal that must be paid for normal costss. As a result, using the benefit cost based on the average for the last 14 years may reduce the amount of funds that must be set aside by the government, reducing the pressure on the government's budget. The prediction of the benefits cost for the needs of the pension fund is obtained from the simulation carried out to obtain the results. The increase and decrease in the nominal fund can be different each year because the number of pension participants is different each year. In addition, it can be seen that the amount of normal cost paid to pension fund participants is higher than the amount of benefits that need to be paid to Lecturers of Civil Servants. The difference between the amount of benefits and normal contributions each year does not show a negative number, so it can be concluded that the normal contributions paid to pension fund companies are sufficient to finance the needs of pension funds for the next 20 years.